Acquisition of technical vocabulary and shipbuilding terminology in chinese didactic environment = Изучение общетехнической и судостроительной терминологии в китайскоязычной дидактической среде - Chernitskiy, V. B.; Черницкий, В. Б.; Jang, Xilai; Жэнг, Ксилаи (My University, 2015)
Didactic problems dealing with masterіng English scientific and shipbuilding terminology by Chinese students have been studied. The study deals with a particular issue of rendering educational services in English as an intermediary language in the Chinese teaching environment. This issue mainly concerns the improvement of teaching process through the development of methodological materials for mastering the fundamental terminology of shipbuilding in the foreign language environment. The key principle for our terminological array selection was based on the intelligible assumption: due to the extension of integration processes of science and technology development and globalization intensification, that are both reflected in the languages of our everyday life, the main attention is to be paid to the mastering of specialized terminology, that of shipbuilding theory and practice fundamentals. It logically resulted in devoting less preference to the general scientific notions and terms as the latter are easily conceived as ‘internationalisms’ in almost all European languages. To substantiate such an assumption we relied on general ways of assimilation in Chinese of the so called ‘internationalisms’ and borrowings from English. In order to prove the validity of this obvious approach we had attempted a brief experiment which demonstrated complete inconsistency of our approach. Thus, the data obtained allow us to solve the aboveindicated problem of CLIL teaching in Chinese didactic environment. = Рассмотрены вопросы усвоения студентами общенаучной и специальной технической терминологии в условиях китайскоязычной дидактической среды. Предложена методика подготовки учебных материалов для повышения качества учебного процесса в среде китайских судостроительных колледжей и ВНЗ.
Черницкий, В. Б. Acquisition of technical vocabulary and shipbuilding terminology in chinese didactic environment = Изучение общетехнической и судостроительной терминологии в китайскоязычной дидактической среде / В. Б. Черницкий, Ксилаи Жэнг // Shipbuilding & Marine Infrastructure. – 2015. – № 1 (3). – C. 164–167.
Keywords: English borrowings; shipbuilding terminology; Content and Language Integrated Learning (CLIL); lexicographic support; английские заимствования; судостроительная терминология; интегрированное изучение иностранного языка на материале содержания специальных дисциплин (CLIL); лексикографическая поддержка